Pengaruh Kelelahan Polarisasi pada Sifat Dielektrik dari Film Polimer Feroelektrik - Limbong, Albinur; Saragih, Horasdia (Jurnal Matematika dan Sains, 2013)
Polimer, seperti polyvinylidene fluoride (PVDF) dan kopolimernya dengan trifluoroethylene (TrFE) adalah material dielektrik dan feroelektrik. Material ini menunjukkan loop histeresis jika dikenakan medan listrik yang disiklus. Agar bersifat  piroelektrik, material ini harus mengalami poling. Perlakuan poling atau fatiguing pada material ini akan mempengaruhi tidak saja sifat feroelektriknya, tetapi juga sifat dielektriknya, baik pada film yang tebal maupun yang tipis (kurang dari 1 mm). Sifat dielektrik yang diukur adalah permitivitas dielektrik dan dielectric loss sebagai fungsi dari frekuensi pada beberapa suhu yang berbeda. Dari hasil pengukuran didapat bahwa poling atau fatiguing meningkatkan kekristalan dan memperbesar ukuran kristal. Tetapi, pengaruh fatigue (kelelahan) pada sifat dielektrik material ini hanya teramati pada frekuensi rendah. Kata kunci: Kelelahan Polarisasi, PVDF, TrFE, Sifat Dielektrik, Polimer Feroelektrik. The Effect of Polarization Fatigue on the Dielectric Properties of Ferroelectric Polymer Films Abstract Polymers, such as Polyvinylidene Fluoride (PVDF) and its copolymers with Trifuoroethylene (TrFE), are both dielectric and ferroelectric materialals. They exhibit polarization hysteresis loop when subjected to cycled electric field. To be pyroelectric, these materialals have to be poled. Poling or fatiguing these materialals influence not only the ferroelectric properties, but also the dielectric properties. This paper reports the Effects of Fatigue on dielectric Properties of PVDF and P(VDF/TrFE) both thick and sub-micron films. The dielectric properties were characterized by the measurement of the dielectric permittivities and loss as function of frequency at several temperatures. Based on the experimental results, it is found that poling the polymers substantially increases the crystallinity and the size of crystallites. However, the effect of fatigue on the dielectric properties is only evident at low frequencies. Keywords: Polarization Fatigue, PVDF, TrFE, Dielectric Properties, Ferroelectric Polymer.